Dampak Hukum Pencurian Karya Melalui Dunia Maya - Nur Ramadhan, Akhmad Rifaldi; Ayunda, Rahmi (Universitas Widya Gama Malang, 2022)
In this digital era, one cSan show the work created through various sites on the internet as examples of several media in cyberspace so that people can admire the created work virtually. However, in this situation there is also a negative side, namely there are parties who are not responsible and do not provide benefits to the creator of the work, because that party uses and takes the artist's copyrighted work for his personal interests which he uses as a commercial thing that benefits him and does not give any royalties to the creator and do not give permission to take the copyrighted work to the artist. In writing this scientific article, there are objectives to be achieved, including knowing and reviewing legal reviews that can be given to creators whose copyrighted works are taken by other people in cyberspace along with the impacts that can be imposed on perpetrators and to find out how to dispute resolution if someone takes a copyrighted work. without the permission of the creator in several online media in cyberspace. The juridical research method used in this research is to examine principles, doctrines, legal norms, and laws that are directly related to intellectual property. The type of approach used in this legal research is the statutory approach, namely by reviewing all laws and regulations that are directly related to related issues in the field of copyright and looking at the comparison of the application of the law with the laws and regulations that have been regulated. and has to do with Copyright. To see the rules set in cases like this